The enjoyment of small-sided games: a narrative review - Clemente, Filipe Manuel (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Small-sided games (SSGs) have become increasingly popular as a training method due to their ability to incorporate game-like, ecological drills that combine technical and tactical development with intense physical and physiological demands. Additionally, SSGs are often favoured in training because they offer engaging and motivating activities for players, closely mimicking the dynamics of actual gameplay. While numerous systematic reviews have examined the acute and chronic effects of SSGs, limited research has explored their impact on player enjoyment. Consequently, the motivational aspects of SSGs are often overlooked in discussions of their benefits. This narrative review aims to address this gap by analysing exist-ing research on the role of enjoyment during SSG implementation. Current evidence suggests that SSGs enhance player enjoyment more effectively than analytical training drills, such as running-based high-intensity interval training, regard-less of the sport. While the format of play does not significantly influence enjoyment, preferences for training regimens vary by sex – boys/men often favour continuous training, while girls/women prefer intermittent formats. Coaches’ verbal en-couragement positively influences enjoyment, but mental fatigue can diminish it. Well-being and recovery status appear to have little effect. Overall, research on enjoyment in SSGs remains limited and often fails to consider important factors, such as motivation and peer interactions. More comprehensive studies are needed to develop a detailed model of enjoyment in SSGs.
Keywords: conditioned games; motivation; constrained games; task constraints